Actual Problems in the Field of Road Traffic Safety (Eurasian Journal of Engineering and Technology, 2022)
This article is devoted to the problems of ensuring road traffic safety, which are gaining urgent importance in our Republic today. The article mentions a number of reasons for the occurrence of road accidents and analyzes the causes of traffic accidents